2003
DOI: 10.1002/cne.10998
|View full text |Cite
|
Sign up to set email alerts
|

Parasympathetic nerve fibers invade the upper dermis following sensory denervation of the rat lower lip skin

Abstract: The sympathetic division of the autonomic nervous system is known to play a role in the genesis of neuropathic pain. In the skin of the rat lower lip (hairy skin), sympathetic and parasympathetic fibers normally innervate the same blood vessels in the lower dermis but do not occur in the upper dermis. However, we have shown that sympathetic fiber migration into the upper dermis occurs following mental nerve lesions (Ruocco et al. [2000] J. Comp. Neurol. 422:287-296). As sensory denervation has a dramatic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 65 publications
1
23
1
Order By: Relevance
“…In other experimental models, parasympathetic innervation of the skin of the lower lip was determined to be limited to blood vessels in the lower dermis. After mental nerve transection, vesicular acetylcholine transporter immunoreactive (VAChT-IR) fibres were observed in the upper dermis, weIl above the opening of the sebaceous glands into the hair follic1es (Ramien et al, 2004). We found that in the glabrous skin of the rat hindpaw, parasympathetic innervation was lacking and immunoreactivity for V AChT was limited to fibres of sympathetic origin at sweat glands (Yen and Ribeiro-da-Silva, unpublished observations).…”
Section: Efferent Nervous Systemmentioning
confidence: 93%
“…In other experimental models, parasympathetic innervation of the skin of the lower lip was determined to be limited to blood vessels in the lower dermis. After mental nerve transection, vesicular acetylcholine transporter immunoreactive (VAChT-IR) fibres were observed in the upper dermis, weIl above the opening of the sebaceous glands into the hair follic1es (Ramien et al, 2004). We found that in the glabrous skin of the rat hindpaw, parasympathetic innervation was lacking and immunoreactivity for V AChT was limited to fibres of sympathetic origin at sweat glands (Yen and Ribeiro-da-Silva, unpublished observations).…”
Section: Efferent Nervous Systemmentioning
confidence: 93%
“…They were then treated with 1% sodium borohydride in PBS and washed extensively in PBS for 60 min. For blocking non‐specific staining, tissue was placed in 10% normal goat serum (NGS) for 60 min and then incubated for 48 h at 4 °C in one of three primary antibodies: mouse monoclonal anti‐dopamine‐β‐hydroxylase (anti‐DBH) [1 : 5; PharmMingen, Canada (Mazzoni et al ., 1991); used to label sympathetic fibres]; a rabbit polyclonal serum against the vesicular acetycholine transporter (VAChT) [1 : 10 000 (Gilmor et al ., 1996) to label parasympathetic fibres] (for a detailed discussion concerning the specificity of this antibody and why we chose VAChT as a marker for cholinergic fibres, see Ramien et al ., 2004); and a rabbit polyclonal anti‐CGRP (1 : 2000; Sigma) as a marker of sensory peptidergic afferent fibres. This antibody was raised against rat CGRP and does not cross‐react with any other peptide except human CGRP and rat and human β‐CGRP (data supplied by Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…In the past, we have found that following complete bilateral transection of the mental nerve (MN), which in rat is a purely sensory nerve of the trigeminal system, both sympathetic and parasympathetic fibres sprout into the sensory denervated upper dermis of rat lower lip skin from which they are normally absent (Ruocco et al ., 2000; Ramien et al ., 2004). The implications of sympathetic sprouting and the ensuing abnormal connectivity between sympathetic and sensory fibres has been well documented as mentioned above; however, less is understood regarding the novel interactions between parasympathetic and sensory neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence for parasympathetic nervous function in the skin is limited to the lower lip, cholinergic nerves are capable of migrating into shallower layers of injured skin. Following sensory denervation, cholinergic (vesicular choline acetyltransferase positive) nerves were shown to migrate into the upper dermis past their normal depth and persist for at least 8 weeks [120, 121]. Whether these sprouting nerves are cholinergic sympathetic or parasympathetic nerves remain unknown.…”
Section: Parasympathetic Control Of the Skinmentioning
confidence: 99%